The Influence of Exports, Exchange Rates (Exchange), Inflation, and Foreign Debt on Foreign Exchange Reserves in Indonesia in 2011-2021: Pengaruh Ekspor, Nilai Tukar (Kurs), Inflasi, dan Utang Luar Negeri Terhadap Cadangan Devisa Di Indonesia Tahun 2011-2021 - Sarifudin Sarifudin (Business Finence Analyst Co.,, 2023)
The purpose of this study is to determine the effect of exports, exchange rates (exchange rates), inflation, and foreign debt on foreign exchange reserves in Indonesia with a vulnerable time from 2011 to 2021. This study uses secondary data, specifically time series data in a period of 11 years. This research is explanatory research because it tries to test the hypothesis between variables. [1] The approach used is quantitative with annual secondary data obtained from official sources of the Central Statistics Agency (BPS), Bank Indonesia (BI) and the world bank from 2011 to 2021. This study uses the Ordinary Least Square (OLS) model using the Eviews 10 application. The results of this study indicate that there is a significant influence of all variables on foreign exchange reserves in Indonesia. However, researchers found inconsistencies with the results that researchers have done on the inflation variable, that results of the partial test of the inflation variable have a positive and significant effect on foreign exchange reserves.